The Influence of Principal's Supervision and Motivation on the Performance of Senior High School Teachers in Tondano - Hana Wagey; Viktory N. J. Rotty; Richard D. H. Pangkey (Riset : Jurnal Ilmiah Multidisiplin Ilmu, 2026)
Kemajuan teknologi digital yang pesat secara mendasar telah membentuk kembali lanskap pengembangan sumber daya manusia (SDM). Artikel ini mengeksplorasi titik temu antara transformasi digital dan pengembangan SDM, dengan fokus pada bagaimana organisasi dapat memanfaatkan teknologi untuk meningkatkan kompetensi karyawan, mendorong pembelajaran berkelanjutan, dan meningkatkan kinerja secara keseluruhan. Berdasarkan tinjauan literatur sistematis, studi ini mengidentifikasi tantangan-tantangan utama—termasuk penolakan terhadap perubahan, kesenjangan keterampilan, dan masalah privasi data—di samping peluang-peluang seperti pembelajaran yang dipersonalisasi, analitik kinerja waktu nyata (real-time), dan peningkatan kelincahan (agility) organisasi. Temuan menunjukkan bahwa keberhasilan pengembangan SDM digital memerlukan keselarasan strategis antara adopsi teknologi, komitmen kepemimpinan, dan budaya belajar sepanjang hayat. Implikasi praktis bagi manajer SDM dan pembuat kebijakan turut dibahas. Kata Kunci : pengembangan sumber daya manusia, transformasi digital, pelatihan karyawan, pembelajaran organisasi, teknologi SDM Teacher performance is the work achievement attained by a teacher in carrying out their duties and responsibilities as an educator according to established professional competency standards. This study aims to determine the influence of principal's supervision and motivation on teacher performance in Tondano: (1) principal's supervision has a significant effect on teacher performance; (2) motivation has a significant effect on teacher performance; (3) principal's supervision and motivation simultaneously have a significant effect on teacher performance. The population in this study were teachers in Tondano. The method used was regression analysis with a sample size of 103 teachers. Data were collected using questionnaires and analyzed using simple and multiple regression techniques tabulated with SPSS for Windows version 25. The results showed that: (1) there is a significant influence of principal's supervision on teacher performance; (2) there is a significant influence of motivation on teacher performance; (3) there is a significant simultaneous influence of principal's supervision and motivation on teacher performance. Based on the research conclusions, it is suggested that: (1) teacher performance needs to be continuously improved; (2) principals need to conduct continuous supervision and enhance teacher work initiative by providing training for self-development, encouraging and motivating continuous growth; (3) schools must create conditions where teachers can optimize their performance.Keywords: Principal's Supervision, Motivation, Senior High School Teacher Performance in Tondano